ANALYSIS OF SPOT-WELDING PITCH ON TOP HAT STRUCTURE AGAINST CRASHWORTHINESS CRITERIA - Harry Purnama; Jos Istiyanto (Majalah Ilmiah Pengkajian Industri, 2021)
The application of spot-welding in the automotive industry, especially the electric-based vehicle frame structure, has been optimized to meet passenger and battery compartment safety factors. The present numerical study of the electric-based vehicle frame structure with the top hat cross-sectional model validated the experimental results of reference, which then modified the spot-welding pitch to determine the crashworthiness effect and criteria. The numerical simulation results show that reducing spot-welding pitch in vertical direction can increase energy absorption (EA) by 1.70% - 9.91%, while bringing spot-welding pitch closer to the flange's outer edge can reduce its maximum force (Fmax) by 8.11% - 21.67%. Keywords: Spot-welding; Top Hat Structure; Crashworthiness; Numerical Simulation; Electric Vehicle.